Critérios de engenharia para classificação de materiais de escavação em valas - Dantas Neto, Silvrano Adonias (2015)
In Brazil, excavation materials in water supply and sanitation works are classified, according to the difficulty offered by their removal, as 1st, 2nd and 3rd category materials, with no well-defined engineering criteria for such classification. This paper aims to present a proposal for excavation material classification based on engineering criteria defined from the results of simple identification surveys (Auger, SPT and rotary surveys). For the purposes of this proposal, a case study was considered that consisted of material classification in the city of Coreaú, State of Ceará, in which there was a conflict about the classification of the materials obtained from excavation. The results have shown that the proposed criteria provide a satisfactory classification of materials in function of current geotechnical tests.